Job Satisfaction of Library Professionals of Higher Educational Institutions in Mizoram: An Analytical Study: Examining Job Satisfaction of Library Professionals in Mizoram (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The present study is limited to the job satisfaction of library professionals with references to higher educational institutions in Mizoram. There is a need to study the job satisfaction of the library professionals because the nature of the job is changing and that job satisfaction is the cause of establishing a healthy working environment in the workplace. This paper focuses on the current job, work allotted, and nature of current work of library professionals, where they report their satisfaction to questions relating to their job. This paper then attempts to analyze the data gathered from library professionals based on a questionnaire survey method. A structured questionnaire was distributed to 31 Central, 26 State, 6 Medical, and 7 Technical library professionals. All the 70library professionals responded to the questionnaires and with the sample and the data analyzed, it shows that Central library professionals are more satisfied with their job and works.